2022
DOI: 10.30630/joiv.6.1.856
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Classification Based on Fundus Images Using Convolutional Neural Network

Abstract: A cataract is a disease that attacks the eye's lens and makes it difficult to see. Cataracts can occur due to hydration of the lens (addition of fluid) or denaturation of proteins in the lens. Cataracts that are not treated properly can lead to blindness. Therefore, early detection needs to be done to provide appropriate treatment according to the level of cataracts experienced. In this study, a comparison of cataract classification based on fundus images using GoogleNet, MobileNet, ResNet, and the proposed Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Simanjuntak et al [27] carried out an investigation to compare the effectiveness of four CNN architectures, specifically MobileNet, ResNet, GoogLeNet, and a custom CNN model, in classifying cataracts using fundus images. The results indicated that the proposed CNN model exhibited the highest level of accuracy and stability with a score of 92%, followed by MobileNet at 92%, ResNet at 93%, and GoogLeNet at 86%.…”
Section: Cataract Detection Using Deep Learning Methodsmentioning
confidence: 99%
“…Simanjuntak et al [27] carried out an investigation to compare the effectiveness of four CNN architectures, specifically MobileNet, ResNet, GoogLeNet, and a custom CNN model, in classifying cataracts using fundus images. The results indicated that the proposed CNN model exhibited the highest level of accuracy and stability with a score of 92%, followed by MobileNet at 92%, ResNet at 93%, and GoogLeNet at 86%.…”
Section: Cataract Detection Using Deep Learning Methodsmentioning
confidence: 99%
“…At the 20th epoch, the training accuracy rate achieved a level of 98.31%, but the validation accuracy rate stood at 96.62%. Simanjuntak et al [8] proposed CNN model achieves the highest level of accuracy (0.93) when the Adam optimizer is applied to a learning rate of 0.001. The model achieves an accuracy of 0.92 for test data and 0.93 for validation data.…”
Section: Introductionmentioning
confidence: 99%
“…When this architecture is adapted to work with In medicine, the application of CNNs can be found in several fields: skin cancer [6], lung diseases [7], heart diseases [8], breast cancer [9], vascular diseases [10], etc. In the case of Ophthalmology, these CNNs have been widely used for the diagnosis of diabetic retinopathy [11], macular degeneration [12], cataracts [13], and glaucoma [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%